2005
DOI: 10.1007/s10654-004-4539-6
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors and lower respiratory tract infection due to respiratory syncytial virus in hospitalised infants in northern Spain

Abstract: Low absolute humidity was independently associated with hospital admission of infants with lower respiratory tract infection due to RSV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
1
25
1
4
Order By: Relevance
“…However, regression models using mean temperature in the preceding month model were not established. In general, the trend of associations between climate factors and respiratory pathogen activity varies with geographic location [35,[48][49][50][51][52][53]. In this study, RSV and HMPV had similar seasonal distribution patterns, and both were negatively correlated with sunshine duration ( Table 2, Fig.…”
Section: Discussionmentioning
confidence: 50%
“…However, regression models using mean temperature in the preceding month model were not established. In general, the trend of associations between climate factors and respiratory pathogen activity varies with geographic location [35,[48][49][50][51][52][53]. In this study, RSV and HMPV had similar seasonal distribution patterns, and both were negatively correlated with sunshine duration ( Table 2, Fig.…”
Section: Discussionmentioning
confidence: 50%
“…However, a variety of factors could influence either the viral survival or infectivity of respiratory viruses, such as meteorological factors, seasonal variations in social behavior, air pollution, and subgroup-specific immune responses throughout (11,13,22,39). Indirectly such factors are important in the rate of detection of respiratory viruses from infants with lower respiratory tract illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Spain (Lapena et al, 2005) indicated that low temperature and low absolute humidity were positively associated with the number of RSV cases and low absolute humidity was independently related to RSV infection. Worldwide, RSV peaks at two temperature intervals: between 2-6°C in temperate regions and 24-30°C in tropical regions.…”
Section: Introductionmentioning
confidence: 99%